HPV Genotype Trends in Iran: Necessity for a Reevaluation of Prevention Strategies - Maryam Shahi; Azam Shafaei; Mohamad Ghodsi; Reza Jafarzadeh Esfehani; Mahdi Moradi Marjaneh (Tropical Medicine and Infectious Disease)
Introduction: Human papillomavirus (HPV) genotyping is critical for preventing and managing HPV-related health issues, including cancers. This study re-evaluates HPV genotype trends in Iran to inform prevention strategies. Materials and Methods: A cross-sectional analysis of HPV genotyping data from individuals tested at the ACECR Khorasan Razavi molecular laboratory in Iran (2016–2022) was conducted, with a forecast of genotype trends through 2027. Results: Among 5009 female patients, 40.4% tested positive for HPV (mean age: 32 ± 8.77 years), with a significant upward trend in positivity over time (tau = 0.905, p = 0.0069). HPV 6, 11, 16, 31, 53, and 54 showed significant increases (p < 0.01), while HPV 66, 84, 67, and 35 exhibited notable trends (p < 0.05). HPV 18 and 33 had marginal trends (p = 0.065, p = 0.052), and HPV 68, 70, and 82 remained stable. Linear regression indicated a non-significant decline in low-risk HPV cases (R = 0.703, p = 0.078) and negligible change in high-risk cases (R = 0.052, p = 0.912). Forecasts predicted increases in HPV 84, 54, 43, 42, and 26, with HPV 6 projected to decrease significantly. HPV 44, 73, and 33 were expected to remain stable. Conclusion: While low-risk HPV cases may decline, the trend lacks statistical significance, and high-risk HPV cases show no change. These findings underscore the need for targeted prevention strategies in Iran, particularly for high-risk genotypes, to reduce the burden of HPV-related cancers. Further research is essential to validate these trends and refine public health interventions.